2012
DOI: 10.2527/jas.53979
|View full text |Cite
|
Sign up to set email alerts
|

The effect of protease and xylanase enzymes on growth performance and nutrient digestibility in finisher pigs

Abstract: Two 2 × 2 factorial experiments were conducted to investigate the interaction between xylanase (0 vs. 200 mg/kg) and protease (0 vs. 200 mg/kg) enzyme supplementation on growth performance (Exp. 1) and coefficient of ileal and total tract apparent digestibility in grower-finisher pigs (Exp. 2). One hundred and twenty-eight individual fed pigs (BW = 34.2 kg; n = 32) were assigned to 1 of 4 dietary treatments: basal diet (T1), T1 + xylanase enzyme (T2), T1 + protease enzyme (T3), or T1 + xylanase + protease enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 2 publications
1
24
1
1
Order By: Relevance
“…Addition of a protease to the diet of broiler chickens has been helpful in optimizing the digestion of undigested protein passing through GIT (Parsons et al 1997;Wang and Parsons 1998;Lemme et al 2004;Angel et al 2011). Some researchers have reported that the addition of protease to swine diet can improve their growth performance (Wang et al 2011;Guggenbuhl et al 2012;McAlpine et al 2012). Our findings showed that the BWG and FCR of chickens fed with low CP diet supplemented with either 0.05% or 0.1% of protease were significantly improved.…”
Section: Discussionmentioning
confidence: 50%
“…Addition of a protease to the diet of broiler chickens has been helpful in optimizing the digestion of undigested protein passing through GIT (Parsons et al 1997;Wang and Parsons 1998;Lemme et al 2004;Angel et al 2011). Some researchers have reported that the addition of protease to swine diet can improve their growth performance (Wang et al 2011;Guggenbuhl et al 2012;McAlpine et al 2012). Our findings showed that the BWG and FCR of chickens fed with low CP diet supplemented with either 0.05% or 0.1% of protease were significantly improved.…”
Section: Discussionmentioning
confidence: 50%
“…However, in several previous studies, no beneficial effects of addition of exogenous protease on growth performance were observed (Thacker ; Mc Alpine et al . ). O'Shea et al .…”
Section: Discussionmentioning
confidence: 97%
“…The results found in the current study are supported by , who reported a negative impact of xylanase addition to liquid feed fermented for 1 h on energy digestibility in weaned pigs. Most of the studies that evaluated the supplementation of NSP enzymes in DDGS-based diets in growing pigs did not report improvements in nutrient digestibility (Mc Alpine et al, 2012;Diebold et al, 2004;Zijlstra et al, 2004).…”
Section: Discussionmentioning
confidence: 99%